1997
DOI: 10.1093/emboj/16.12.3386
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human glyoxalase I_evidence for gene duplication and 3D domain swapping

Abstract: Glyoxalase I (EC 4.4.1.5) catalyses the isomerization Sweden of the thiohemiacetal of glutathione (GSH) and a 2 Corresponding author 2-oxoaldehyde into the thiolester of GSH and the corresponding 2-hydroxycarboxylic acid. The substrate of the The zinc metalloenzyme glyoxalase I catalyses the reaction, the thiohemiacetal, is formed non-enzymatically. glutathione-dependent inactivation of toxic methylGlyoxalase II then hydrolyses the thiolester to produce glyoxal. The structure of the dimeric human enzyme GSH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
219
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(227 citation statements)
references
References 52 publications
6
219
0
2
Order By: Relevance
“…This residue is close to the Glu111 that is replaced by the SNP. The 3D structure of Glo1 with Glu111 has shown that the active Glo1 functions as a dimer with the two zinc atoms, two active sites as well as two glutathione-binding sites formed at the interface [Cameron et al, 1997]. Although, these studies have not shown direct interaction of Glu111 in zinc binding, any chemical interactions that change the 3D structure or disrupt electrostatic bonds are expected to affect enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…This residue is close to the Glu111 that is replaced by the SNP. The 3D structure of Glo1 with Glu111 has shown that the active Glo1 functions as a dimer with the two zinc atoms, two active sites as well as two glutathione-binding sites formed at the interface [Cameron et al, 1997]. Although, these studies have not shown direct interaction of Glu111 in zinc binding, any chemical interactions that change the 3D structure or disrupt electrostatic bonds are expected to affect enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…Domain swapping has been proposed as a possible mechanism for protein aggregation (5). Further, it may be a novel regulatory motif for protein function § (6)(7)(8) as well as a simple evolutionary strategy for evolving oligomers from monomers (9)(10)(11).…”
mentioning
confidence: 99%
“…Each active site contains one zinc(II) ion, coordinated by 4 amino acids and one molecule of water. The coordination symmetry is close to square pyramidal with 3 amino acids and the water in the plane and the fourth amino acid as the axial ligand (5).…”
mentioning
confidence: 99%